Electrophysiologic Signs of Auditory Distraction in Elderly Listeners - Fisher, Amy L.; Hymel, Murvin R.; Cranford, Jerry L.; DeChicchis, Albert R. (Journal of the American Academy of Audiology, 2000)
Brain mapping was used to investigate the ability of young and elderly female listeners to attend to /ga/ syllabic events at one ear in the presence of speech babble competition at the opposite ear. An oddball stimulus presentation paradigm was used to record the N1 and P2 components of the late auditory evoked potential (LAEP) from 19 scalp locations. With speech competition, elderly listeners exhibited significantly larger reductions in R, amplitude than did young listeners. The competition produced no changes in N1 amplitude in either group. These findings contrast with those of an earlier study in which age-related reductions in N1 but not P2 amplitude were found when listeners attended to tones rather than speech stimuli in the presence of speech competition. These studies suggest that amplitude reductions in different LAEP components may provide electrophysiologic indices of age-related breakdowns in processing sounds in the presence of competition. Which LAEP components are affected may depend on experimental variables such as task difficulty or the nature of the stimuli (e.g., speech vs nonspeech).Abbreviations: ANOVA = analysis of variance, CID = Central Institute for the Deaf, EEG = electroencephalographic activity, GFP = global field power, LAEP = late auditory evoked potential, PTA = average of pure-tone threshold hearing levels at 500, 1000, and 2000 Hz, SL = sensation level, SRT = speech reception threshold, WRS = word recognition score
Keywords: Auditory distraction; auditory event-related potentials; auditory evoked potentials; brain map, elderly listeners; N1 processing negativity; P2; P300; scalp topography; selective attention; speech competition